Life balance and traumatic txperiences in undergraduate students living near conflict zones - Karaman, Mehmet Akif; Aydın, Gül; Sarı, Halil İbrahim (Springer, 2020)
This study aimed to examine the prevalence of PTSD among undergraduate students and how PTSD affected life balance of undergraduate students who live close to conflict zones. The participants of the study were 253 undergraduate students who lived close to conflict zone and witnessed or experienced bombing or war conflicts. Data collection instruments were Juhnke-Balkin Life Balance Inventory- Turkish Form and Turkish Version of the PTSD Checklist for Diagnostic and Statistical Manual of Mental Disorders Fifth Edition. The data were collected in paper-pencil format one month after bombing by terrorists across the border. Structural equation modeling was used in data analysis. The results indicated that PTSD symptomatology positively affects the students’ depression and sleep disturbance levels. However, PTSD symptomatology negatively affects global health and positive orientation. All effect sizes were in small to large range. We suggest that administrators should invest counseling services and have practioners providing help especially for undergraduate students in conflict zones; and to make families familiar with PTSD symptoms. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Conflict zones; Life balance; Post-traumatic stress disorder; Trauma; Turkey